Crystal structure of RNase H3–substrate complex reveals parallel evolution of RNA/DNA hybrid recognition - Figiel, Małgorzata (Oxford University Press, 2014)
RNases H participate in the replication and maintenance of genomic DNA. RNase H1 cleaves the RNA strand of RNA/DNA hybrids, and RNase H2 in addition hydrolyzes the RNA residue of RNA–DNA junctions. RNase H3 is structurally closely related to RNases H2, but its biochemical properties are similar to type 1 enzymes. Its unique N-terminal substrate-binding domain (N-domain) is related to TATA-binding protein. Here, we report the first crystal structure of RNase H3 in complex with its RNA/DNA substrate. Just like RNases H1, type 3 enzyme recognizes the 2′-OH groups of the RNA strand and detects the DNA strand by binding a phosphate group and inducing B-form conformation. Moreover, the N-domain recognizes RNA and DNA in a manner that is highly similar to the hybrid-binding domain of RNases H1. Our structure demonstrates a remarkable example of parallel evolution of the elements used in the specific recognition of RNA and DNA.